HUBUNGAN MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DENGAN MOTIVASI BELAJAR SISWA - Andi Agustan Arifin; Sri Ratnasari (STKIP Andi Matappa, 2017)
The purposes of this research were to know the description of the student's interest in continuing education to college, to know the description of learning motivation of XII grade students of SMA Negeri 3 Wayaluba Morotai and to know the correlation of interest in continuing education with students’ learning motivation of SMA Negeri 3 Wayaluba Morotai. The population in this study is 200 students. Samples were taken by using proportional random sampling. The amount of sample was set as many as 20% of the population so that the retrieved sample is 40 students. The technique of data collection was questionnaire. Techniques of data analysis in this study used descriptive statistics analysis and correlation analysis using statistic correlation analysis in the form of parametric product moment. The results showed that the students’ interest in continuing education to college of SMA Negeri 3 Wayabula Morotai was in high category of student learning and motivation was also in high category. There was a significant positive relationship between the interest in continuing education and the study motivation of the XII grade students of SMA Negeri 3 Morotai Wayabula which were in the category of very strong based on the interpretation of the value of r, since the value of r count of 0.900 so be at intervals of 0800-1,000 or category of very strong.